Racing for Innocence : Whiteness, Gender, and the Backlash Against Affirmative Action. - Pierce, Jennifer (Stanford University Press, 2012)
& DIV & How is it that recipients of white privilege deny the role they play in reproducing racial inequality? & I & Racing for Innocence & /I & addresses this question by examining the backlash against affirmative action in the late 1980s and early 1990s-just as courts, universities, and other institutions began to end affirmative action programs. & BR & & BR & This book recounts the stories of elite legal professionals at a large corporation with a federally mandated affirmative action program, as well as the cultural narratives about race, gender, and power in the news media and Hollywood films. Though mos.